2011
DOI: 10.1007/jhep06(2011)087
|View full text |Cite
|
Sign up to set email alerts
|

On the effective description of large volume compactifications

Abstract: Abstract:We study the reliability of the Two-Step moduli stabilization in the type-IIB Large Volume Scenarios with matter and gauge interactions. The general analysis is based on a family of N = 1 Supergravity models with a factorizable Kähler invariant function, where the decoupling between two sets of fields without a mass hierarchy is easily understood. For the Large Volume Scenario particular analyses are performed for explicit models, one of such developed for the first time here, finding that the simplif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 76 publications
(254 reference statements)
2
36
1
Order By: Relevance
“…(2.3)). Of these, the S and the U -moduli can be stabilised at leading order in g s and α ′ if nonzero 3-form fluxes are present in the background geometry [5,35]. By contrast, the Kähler moduli T i remain unstabilised at leading semiclassical order.…”
Section: Boilerplate Kähler-modulus Stabilisationmentioning
confidence: 99%
“…(2.3)). Of these, the S and the U -moduli can be stabilised at leading order in g s and α ′ if nonzero 3-form fluxes are present in the background geometry [5,35]. By contrast, the Kähler moduli T i remain unstabilised at leading semiclassical order.…”
Section: Boilerplate Kähler-modulus Stabilisationmentioning
confidence: 99%
“…Under these circumstances (3.10) does not imply λ I = |W |, and generically, the complex structure moduli and the axio-dilaton are stabilised at the scale O max(e K λ 2 I , e K |W | 2 ) for each λ I . These moduli are then generically decoupled from the details of the Kähler moduli stabilisation [73][74][75].…”
Section: Anti-de Sitter Vacua In the Large Volume Scenariomentioning
confidence: 99%
“…The implications of this equation are again very important: the three-form fluxes can stabilise most of the fields in the complex structure and axiodilaton sector with squared masses of ∼ 1/V 2 min , but a consistent inclusion of the additional 5 The existence of run-away directions in the moduli space has since long been identified as a critical aspect of string compactifications [76]. A detailed analysis of the FIF I ∼ |W | 2 case is intricate: for comparatively small volumes and large supersymmetry breaking the various contributions to the potential become of similar magnitude and couplings between the axio-dilaton, complex structure and the Kähler moduli are all important [73,74]. Moreover, the applicability of the four-dimensional N = 1 supergravity as an effective description of the low-energy theory becomes questionable as the hierarchy between the compactification scale and the supersymmetry breaking scale decreases.…”
Section: Large Volume Extremamentioning
confidence: 99%
“…Then, for instance, in a model proposed by Cremades et al in [37], an F-term from a matter-like field serves as uplifting for the cosmological constant. However, later studies by the author showed that such model fails in getting an dS/Minkowski [39]. In other words the uplifting procedure does not achieve its target.…”
Section: Introductionmentioning
confidence: 99%